Geochimic Study of Geological Formations of Sake (Kibarian) In North-Kivu, R.D.Congo - Kavyavu, K.W.; Simba, A.; Nathati, M.L. (Algerian Journal of Research and Technology (AJRT), 2018)
The geochemical study of the facies of Sake in the Masisi Territory is as for any area a preliminary concept that may serve as a preliminary level for the valuation of the mining anomalies that can have this region. Our study focused on the trace elements to find their concentration in the petrography diversity and allows to have an idea on the metalogeny model of this anomaly trace establishment, in our case, is veinous given the gold content in the units may belong to the hydrothermal concentrations in the breaks. It’s just demonstrated from the standardized contents that Sake is highly stano-auriferous and poorly in Niobite- Tantalum parageneses.